Training Needs and Preferences of Social Workers Providing Services to Migrant Children - Mataitytė-Diržienė, Jurga; Ališauskaitė, Vaida (Socialinė teorija, empirija, politika ir praktika, 2020)
A recent wave of migration has brought a lot of children to the EU. Children in migration face a stronger risk of becoming victims of violence, physical or sexual abuse, and trafficking. Social workers in the receiving countries are usually the ones who most often provide services to them. The study, using focus group methodology and aiming to identify the needs of social workers for training and their training preferences in this context, was carried out in 2018, in 7 EU countries. The results have shown that the main issue is the absence of specific, systemic training aimed at improving the knowledge and skills needed for work with migrants. The public or governmental institutions did not have an interest in providing such kinds of training, they were organized on an ad-hoc basis by NGOs mainly. Lack of knowledge about legal systems, the difference between the theory and practice, and the lack of practical experience working with migrant minors were named by participants as the main gaps that need improvement.